Crosstalk between core-multishell nanocarriers for cutaneous drug delivery and antigen-presenting cells of the skin. (April 2018) - Edlich, Alexander; Volz, Pierre; Brodwolf, Robert; Unbehauen, Michael; Mundhenk, Lars; Gruber, Achim D.; Hedtrich, Sarah; Haag, Rainer; Alexiev, Ulrike; Kleuser, Burkhard
Abstract: Owing their unique chemical and physical properties core-multishell (CMS) nanocarriers are thought to underlie their exploitable biomedical use for a topical treatment of skin diseases. This highlights the need to consider not only the efficacy of CMS nanocarriers but also the potentially unpredictable and adverse consequences of their exposure thereto. As CMS nanocarriers are able to penetrate into viable layers of normal and stripped human skin ex vivo as well as in in vitro skin disease models the understanding of nanoparticle crosstalk with components of the immune system requires thorough investigation. Our studies highlight the biocompatible properties of CMS nanocarriers on Langerhans cells of the skin as they did neither induce cytotoxicity and genotoxicity nor cause reactive oxygen species (ROS) or an immunological response. Nevertheless, CMS nanocarriers were efficiently taken up by Langerhans cells via divergent endocytic pathways. Bioimaging of CMS nanocarriers by fluorescence lifetime imaging microscopy (FLIM) and flow cytometry indicated not only a localization within the lysosomes but also an energy-dependent exocytosis of unmodified CMS nanocarriers into the extracellular environment. Graphical abstract: